The fail-safe startup - Eisenmann, Tom. (London : Penguin Business, 2021)
Why do most startups fail? Eisenmann has focused his research, and his MBA class at Harvard University, on the mistakes and missteps of entrepreneurs and founders for the past decade.For the first time, he reveals his findings, and - most importantly - how you can avoid them. Drawing on case studies from startups from around the world, The Fail-Safe Startup reveals how to analyse others' failure to ensure your success.
Keywords: New business enterprises; Entrepreneurship